Submucosal tunneling endoscopic resection for an esophageal bronchogenic cyst. Issue Volume 33:Issue S1(2021) (5th January 2022) - Dong, Tao; Fan, Wentao; Tao, Yuwen; Liu, Li; Fan, Zhining
Abstract : Supplemental Digital Content is available in the text.